2015
DOI: 10.1007/s10882-015-9439-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Parenting Stress in Children Referred for an Autism Spectrum Disorder Diagnostic Evaluation

Abstract: Parents of children with autism spectrum disorder (ASD) report significantly higher stress than parents of children with other developmental disorders. Symptoms that overlap with the autism spectrum are often present in other developmental disorders, which could significantly increase parenting stress. Additionally, the severity of ASD symptoms within a group of children with ASD can greatly vary. In the present study, problem behaviors, cognitive and adaptive functioning, and parenting stress were examined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 46 publications
(66 reference statements)
2
24
0
Order By: Relevance
“…Having a mentally disabled child in the family is a stressor that causes an emotional burden, a stressful life experience and requires continuous coping reactions to all family members (Ayyildiz et al, 2012; Gordeles-Beser & Inci, 2014; Yildirim-Dogru & Arslan, 2008). Having a mentally disabled child is a difficult life event with the need for development of existing coping skills and increased need for social support (Brei et al, 2015; Dardas & Ahmad, 2015; Gulsen & Gok-Ozer, 2009; Konukbay & Arslan, 2015; Kucuk & Kucuk-Alemdar, 2018; Singh et al, 2015). Difficulties in the increasing care needs of children with mental disabilities, difficulties in education needs, the insecurity of the future (Brei et al, 2015; Dabrowska & Pisula, 2010; Dardas & Ahmad, 2015; Gordeles-Beser & Inci, 2014; Gulsen & Gok-Ozer, 2009; Konukbay & Arslan, 2015; Kucuk & Kucuk-Alemdar, 2018; Lu et al, 2018; Singh et al, 2015) and the difference between healthy child expectation and reality increase the pain and emotional reactions of the family (Dabrowska & Pisula, 2010; Dardas & Ahmad, 2015; Gordeles-Beser & Inci, 2014; Lu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Having a mentally disabled child in the family is a stressor that causes an emotional burden, a stressful life experience and requires continuous coping reactions to all family members (Ayyildiz et al, 2012; Gordeles-Beser & Inci, 2014; Yildirim-Dogru & Arslan, 2008). Having a mentally disabled child is a difficult life event with the need for development of existing coping skills and increased need for social support (Brei et al, 2015; Dardas & Ahmad, 2015; Gulsen & Gok-Ozer, 2009; Konukbay & Arslan, 2015; Kucuk & Kucuk-Alemdar, 2018; Singh et al, 2015). Difficulties in the increasing care needs of children with mental disabilities, difficulties in education needs, the insecurity of the future (Brei et al, 2015; Dabrowska & Pisula, 2010; Dardas & Ahmad, 2015; Gordeles-Beser & Inci, 2014; Gulsen & Gok-Ozer, 2009; Konukbay & Arslan, 2015; Kucuk & Kucuk-Alemdar, 2018; Lu et al, 2018; Singh et al, 2015) and the difference between healthy child expectation and reality increase the pain and emotional reactions of the family (Dabrowska & Pisula, 2010; Dardas & Ahmad, 2015; Gordeles-Beser & Inci, 2014; Lu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Having a mentally disabled child in the family is a stressor that causes an emotional burden, a stressful life experience and requires continuous coping reactions to all family members (Ayyildiz et al, 2012;Gordeles-Beser & Inci, 2014;Yildirim-Dogru & Arslan, 2008). Having a mentally disabled child is a difficult life event with the need for development of existing coping skills and increased need for social support (Brei et al, 2015;Dardas & Ahmad, 2015;Gulsen & Gok-Ozer, 2009;Konukbay & Arslan, 2015;Kucuk & Kucuk-Alemdar, 2018;Singh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raising a child with autism spectrum disorder (ASD) can exert tremendous stress on parents (Davis and Carter 2008) given that the core features of ASD include impaired social communication, restricted interests, and repetitive behaviors (American Psychiatric Association 2013). Numerous studies have demonstrated that these families experience more stress than families with typically developing children or children with other special needs (e.g., Brei et al 2015; Falk et al 2014). Although these findings are unsurprising given the chronic nature of the challenging behaviors associated with ASD, they emphasize the importance of identifying factors that may contribute to the stress that parents perceive and the degree to which such stress might affect their actual parenting behaviors (Hayes and Watson 2013; Keenan et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Parents of children that diagnosed with behavioral disorders or developmental disabilities are at risk of parenting stress (Brei et al, 2015). Parents of children with autism spectrum disorders or developmental abnormalities reported had higher levels of parenting stress than parents of children whose development tended to be normal (Hutchison et al, 2016).…”
Section: Introductionmentioning
confidence: 96%